ANALISIS MODEL TA’DIB DALAM PEMBELAJARAN ISLAM - Ita Tryas Nur Rochbani (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Problems that will be studied in this research, that is: model of ta'dib based PAI curriculum policy in improving student learning and its supporting and inhibiting factors. This research is motivated by the problem kuranngnya role of government, parents and teachers in education. Which one puts forward the cognitive domain and puts aside the importance of adab in measuring student success. The purpose of education is to give birth to a perfect human being that is civilized human (kamil man). The ta'dib curriculum can improve students 'learning by two main factors namely learning method (ie using Tauhid Method) and learning materials that are in accordance with the target of Islamic religious education (ie fardu' ain) and rational, intellectual and philosophical (fardhu kifayah).The factors supporting and inhibiting the ta'dib-based curriculum are: 1) Parents who look far ahead, the importance of character and the planting of religious knowledge from an early age, 2) Some of the educators who want the next generation of nation has a noble character and always leading to the norms according to the religious shari'a, 3) Some governments who agree on the ta'dib-based curriculum can be applied in every educational institution. While Inhibiting Factors Policy of PAI Based Ta'dib curriculum, are: 1) Problem of concept or thinking of government which is more concerned with cognitive aspect compared with process or ta'dibnya learners, 2) Purpose of parent who put forward the cognitive domain, so forget about character and the behavior of children, 3) The era of continuous changes and the era of globalization is high, so the child's cognitive importance of the child's character